Determinants of Mortgage Loan Approval in Banks in a Developing Country: Evidence From Nigeria - Babalola, Abdurrauf; Ajagbe, Suraj (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2024)
This article is aimed at investigating the determinants of mortgage loan approval in developing countries, employing the binary probit model. Loan approval was made the response variable while deposit, amount to borrow, lending rate, gratuity, capacity to pay the loan and character of the borrowers stood as the explanatory variables. Cross-sectional data were collected from the four top banks in Nigeria. The result showed that all the variables had the correct signs but only the capacity to pay the loan has a significant impact in determining the success of mortgage loan approval. Collectively, all the variables have significant power to determine mortgage loan approval. It is therefore suggested that prospective borrowers should ensure that they have all it takes to refund the loan they wish to obtain from commercial banks.